STUDENTS’ PERCEPTIONS ON THE USE OF YOUTUBE TO LEARN ENGLISH POST-PANDEMIC - Laily Esti Sofiana; Wahyu Diny Sujannah; Didik Hartono (JURNAL PENDIDIKAN GLASSER, 2023)
YouTube can be a preferable media for effective and engaging English learning. This survey research was conducted to investigate the students’ perceptions on the use of YouTube to learn English post-pandemic. The participants were 88 second-grade students in one of the public junior high schools in Batu. The data were taken by administering the questionnaire directly to the students. The findings revealed that YouTube was effective, attractive, and motivating to help the students learn English post-pandemic in the classroom. Thus, it is recommended that English teachers teach English by means of YouTube in their class. Moreover, it is also suggested that future researchers investigate whether the students’ perceptions on the use of YouTube will differ across their learning styles